FREQUENCY OF ASYMPTOMATIC HYPOCALCEMIA IN POST-THYROIDECTOMY PATIENTS: AN EXPERIENCE IN TERTIARY CARE HOSPITAL - AZEEM , S; SHAHEEN , U; ANWAR , M; AKHTAR , N; RASHEED , U; ULLAH , S (Biological and Clinical Sciences Research Journal, 2024)
Hypocalcemia is a frequent and clinically significant complication following total thyroidectomy. While most cases are transient and asymptomatic, persistent hypocalcemia can lead to prolonged hospital stays, increased healthcare costs, and reduced quality of life. Identifying the predictors of postoperative hypocalcemia is essential for early diagnosis, prevention, and management Objective: To assess the incidence and predictors of hypocalcemia in patients undergoing total thyroidectomy. Methods: A prospective study was conducted in the Surgical Ward of Nishtar Hospital Multan from April 2024 to September 2024. A total of 100 patients with thyroid carcinoma, thyroid nodules, or thyroiditis undergoing total thyroidectomy were included in the study. Surgical factors, clinical effects, patient characteristics, and pathological variables were explored to determine their impact on post-operative thyroidectomy which was defined as a serum calcium level less than 2.1 mmol/ Results: 65 (65%) patients developed postoperative hypocalcemia among which 75.4% had asymptomatic hypocalcemia. An occurrence of a thyroid storm less than 10 years before the study was significantly associated with the development of hypocalcemia (p=0.049). Ligation of the trunk of the left (p=0.005) and right inferior thyroid artery (p<0.001), number of parathyroid glands (p<0.001), and auto-transplanted PGs (p=0.020) were also significant risk factors of hypocalcemia. Lastly, PTH level on day 1 postop was also a strong predictor (p<0.001. Multivariate regression model showed old age (p=0.032) and female sex (p=0.041) as significant independent risk factors of hypocalcemia. Conclusion: There is a high incidence of postoperative asymptomatic hypocalcemia in patients undergoing total thyroidectomy. Patients’ demographic factors including age, sex, and occurrence of thyrotoxicosis, and surgical factors including intraoperatively identified PGs, preoperative calcium and ionized calcium levels, PTH within first 24 hours postop, and ligation of the trunk of left and right inferior thyroid artery were significant risk factors.